Strategi Bertahan Hidup Janda di Bawah Umur - Wafa Suci Ningrum; Miftahul Huda; Rohmah Maulidia (Institut Agama Islam Negeri Ponorogo, 2025)
This research is motivated by the increasing number of early-age divorce cases, which has resulted in many young women becoming underage widows—girls under 19 years old who have already experienced marriage and divorce, and most of whom already have children. This study is a field research using a case study approach. The data were collected from primary sources such as underage widows, their parents, and representatives from the Women's Empowerment and Child Protection Agency (P3A) and secondary sources, including documents, legislation, and relevant literature. The research was conducted in the Ponorogo, Madiun, and Nganjuk Regencies, with the implementation adjusted to the availability and conditions of the informants. Data collection techniques included in-depth interviews, observation, and documentation. Data analysis was carried out using the Miles and Huberman model, which involves data reduction, data presentation, and continuous drawing of conclusions throughout the research process. The findings show that some underage widows can utilize their livelihood assets to implement consolidation, active, and passive strategies, while others can only survive using basic survival strategies. Most choose to work and pursue education through the Package C program. Although these young widows can endure, they still face significant challenges, and some eventually decide to remarry as a way out of life’s pressures. Underage widows adopt survival strategies rationally, based on their conditions and available resources—by working, continuing education, or remarrying—as a way to cope with pressure and build a future.